SCREENING OF MULBERRY (MORUS) GERMPLASM ACCESSIONS FOR PROPOGATION PARAMETERS - MADHURI THINNALURI, NARAYANASWAMY, T. K. JYOTI BIRADAR CHIKKALINGAIAH, (The Bioscan, 2015)
Eighteen mulberry genotypes were field tested at Department of Sericulture, UAS, GKVK, Bangalore, Karnataka. These mulberry genotypesviz., V-1, M-5, DD-1, S-34, Mysore Local, MR2, S-36, S-54, RFS-135, RFS-175, S-41, S-13, MI-11, M. Indica, Dudia white, UP-105, Himachal local and MS-3 were evaluated for the propagation parameters, like, survival, shoot growth and rooting behaviour. Results showed that,survival rate was above 75% was recorded in UP, MR-2, S-13, M5 and V-1. Mulberry variety V-1 recorded highest shoot length of 51.61cm and shorter shoot length was recorded in S-54 (16.99 cm). Mulberry varieties studied exhibited considerable variations in fresh shoot and dry shoot weight. Among the mulberry varieties studied, DWshowed the longest root length, (18.11 cm), more numbers of roots/sapling (13.8) highest fresh weight (2.75 gm) and Root volume (3.37 ml) when compared to othergenotypes and UP showing least values with respect to all these root traits. So, these two genotypes will use as a parents for making root specific mapping population for further genomic studies.